2015
DOI: 10.1177/000313481508100101
|View full text |Cite
|
Sign up to set email alerts
|

Racial Disparities in the Use of Laparoscopic Cholecystectomy Still Exist!

Abstract: Brief Reports should be submitted online to www.editorialmanager.com/ amsurg. (See details online under ''Instructions for Authors''.) They should be no more than 4 double-spaced pages with no Abstract or sub-headings, with a maximum of four (4) references. If figures are included, they should be limited to two (2). The cost of printing color figures is the responsibility of the author.In general, authors of case reports should use the Brief Report format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
1
1
Order By: Relevance
“…In an early study that compared the use of laparoscopy between black patients and white patients within the Veterans Affairs medical centers from 1992 to 1995, black patients were approximately 25 per cent less likely than white patients to undergo a laparoscopic rather than open cholecystectomy. 5 In a subsequent study using the 2005 to 2010 Nationwide 6 In our study, however, there was no difference in the use of laparoscopy between non-white and white patients on adjusted analysis. Although our study design was different (we compared whites to everyone else and not whites to blacks), our results using more recent data suggest that the racial disparity in access to laparoscopic cholecystectomy may be disappearing.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…In an early study that compared the use of laparoscopy between black patients and white patients within the Veterans Affairs medical centers from 1992 to 1995, black patients were approximately 25 per cent less likely than white patients to undergo a laparoscopic rather than open cholecystectomy. 5 In a subsequent study using the 2005 to 2010 Nationwide 6 In our study, however, there was no difference in the use of laparoscopy between non-white and white patients on adjusted analysis. Although our study design was different (we compared whites to everyone else and not whites to blacks), our results using more recent data suggest that the racial disparity in access to laparoscopic cholecystectomy may be disappearing.…”
Section: Discussioncontrasting
confidence: 48%
“…3,4 Previous studies have shown that black patients, compared with white patients, were significantly less likely to undergo a laparoscopic rather than open cholecystectomy. 5,6 Among patients with gallstone pancreatitis, black and Asian patients were less likely to undergo cholecystectomy compared with risk-adjusted white patients. 7 However, there is a paucity of data about how race affects the surgical outcomes of gallbladder disease.…”
mentioning
confidence: 99%